Efficient algorithms for solving nonlinear Volterra integro-differential equations with two point boundary conditions - L. E. Garey; R. E. Shaw (International Journal of Mathematics and Mathematical Sciences)
In this paper a collection of efficient algorithms are described for solving an algebraic system with a symmetric Toeplitz coecient matrix. Systems of this form arise when approximating the solution of boundary value Volterra integro-differential equations with finite difference methods. In the nonlinear case, an iterative procedure is required and is incorporated into the algorithms presented. Numerical examples illustrate the results.